2010
DOI: 10.1093/brain/awq055
|View full text |Cite
|
Sign up to set email alerts
|

Remote memory deficits in transient epileptic amnesia

Abstract: Transient epileptic amnesia is a form of temporal lobe epilepsy in which sufferers often complain of irretrievable loss of remote memories. We used a broad range of memory tests to clarify the extent and nature of the remote memory deficits in patients with transient epileptic amnesia. Performance on standard tests of anterograde memory was normal. In contrast, there was a severe impairment of memory for autobiographical events extending across the entire lifespan, providing evidence for the occurrence of 'foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 46 publications
3
46
0
7
Order By: Relevance
“…Remarkably, this is precisely the pattern of memory impairment recently reported in the syndrome of TEA (Zeman, Butler, Muhlert, & Milton, 2013;Hoefeijzers et al, 2014;Dewar et al, 2014;Milton et al, 2010). In CS's case the transient memory impairment and ALF resolved with withdrawal of baclofen, while her AbA has persisted.…”
Section: Main Findingssupporting
confidence: 74%
“…Remarkably, this is precisely the pattern of memory impairment recently reported in the syndrome of TEA (Zeman, Butler, Muhlert, & Milton, 2013;Hoefeijzers et al, 2014;Dewar et al, 2014;Milton et al, 2010). In CS's case the transient memory impairment and ALF resolved with withdrawal of baclofen, while her AbA has persisted.…”
Section: Main Findingssupporting
confidence: 74%
“…El grado de amnesia retrógrada que se experimenta varía con el individuo. Los pacientes con AET presentan déficits en la memoria episódica autobiográfica, memoria semántica (tanto para hechos personales como públicos y memoria anterógrada (2,20).…”
Section: Neuropsicologíaunclassified
“…Incluye la memoria episódica (autobiográfica, que permite al sujeto revivir los eventos recordados) y la memoria semántica (datos, tanto de realidades personales como públicas (1,20).…”
Section: Memoria Remotaunclassified
See 1 more Smart Citation
“…In both these conditions, patients often have normal anterograde episodic memory with frequent impairment of autobiographical memory 10,11 . Recently, Coras et al 12 have demonstrated that hippocampal sclerosis patients with greater neuronal loss in CA3, CA4 and the dentate gyrus have a predominant loss of anterograde memory, and that, conversely, those with predominant neuronal loss in CA1 generally have normal anterograde memory.…”
mentioning
confidence: 99%